2018
DOI: 10.1159/000485127
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Clinical Presentation of Anaphylaxis in Singapore: From Infancy to Old Age

Abstract: Background: The study objective was to compare age-related differences in the cause and clinical presentation of anaphylaxis. Methods: We conducted a prospective study of patients visiting the emergency department for anaphylaxis. Data were collected from 3 emergency departments from 1 April 2014 to 31 December 2015. Patient electronic records with the diagnoses of allergy, angioedema, urticaria, and anaphylaxis (ICD-9 codes 9953, 9951, 7080, 9950, 7089) were screened and cases fulfilling World Allergy Organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
4
25
0
1
Order By: Relevance
“…In addition, an accurate diagnosis of anaphylaxis in children can prove challenging. This is partially due to the inability of children to accurately describe their symptoms, the lack of cutaneous symptoms in up to 40% of drug‐induced cases, the lack of tryptase measurement in most cases, and difficulties in accurately evaluating blood pressure, especially in infants . A recent work on pediatric anaphylaxis presenting at an ED showed that almost 50% of the diagnosis are actually missed .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an accurate diagnosis of anaphylaxis in children can prove challenging. This is partially due to the inability of children to accurately describe their symptoms, the lack of cutaneous symptoms in up to 40% of drug‐induced cases, the lack of tryptase measurement in most cases, and difficulties in accurately evaluating blood pressure, especially in infants . A recent work on pediatric anaphylaxis presenting at an ED showed that almost 50% of the diagnosis are actually missed .…”
Section: Epidemiologymentioning
confidence: 99%
“…This is partially due to the inability of children to accurately describe their symptoms, the lack of cutaneous symptoms in up to 40% of drug-induced cases, the lack of tryptase measurement in most cases, and difficulties in accurately evaluating blood pressure, especially in infants. [8][9][10][11][12] A recent work on pediatric anaphylaxis presenting at an ED showed that almost 50% of the diagnosis are actually missed. 13 Thus, reports on general anaphylaxis incidence in pediatric ages have a wide variation in number from 10.5 to 70 episodes per 100 000 person-years.…”
Section: Epidemi Ologymentioning
confidence: 99%
“…Studies with data on anaphylaxis treatment modalities and the prevalence of biphasic anaphylaxis among the studies with available data are summarized in Table S2 3,6,8,10,12,13,23,24,31,33,36,39,41,54 and Table S3, 3,6,8,10,12,13,23,30,31,33,52,55,56 respectively. Few studies were able to identify predictors of biphasic anaphylaxis.…”
Section: Anaphylaxis Fatalities Remain Low Globallymentioning
confidence: 99%
“…In-hospital adrenaline (epinephrine) use for the treatment of anaphylaxis was generally low across most studies, except for Canada and Singapore. 8,24,55 Several studies also highlighted a preponderance of inappropriate adrenaline dosing, such as subcutaneous, inhalational, and intravenous routes of administration (bolus and infusion) instead of the gold-standard intramuscular route advocated in anaphylaxis treatment guidelines. 3,6,8,33 There were high rates of steroid and antihistamine administration, which exceeded the usage of adrenaline in almost all the studies.…”
Section: Anaphylaxis Is Still Under-treated Across the Worldmentioning
confidence: 99%
“…Food allergy occurred more often in children, while drug anaphylaxis was more common in adults. There was an age-dependent shift of clinical presentations with gastrointestinal symptoms in infants and young children, respiratory symptoms in schoolchildren and adolescents, and cardiovascular symptoms in adults [97]. A cross-sectional study revealed symptoms of sting reactions in 13% of the overall population, of which half had systemic reactions.…”
Section: Identifying and Managing Anaphylaxismentioning
confidence: 99%